2019
DOI: 10.1111/jnc.14665
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal KIF5b deletion induces striatum‐dependent locomotor impairments and defects in membrane presentation of dopamine D2 receptors

Abstract: The process of locomotion is controlled by fine-tuned dopaminergic neurons in the Substantia Nigra pars-compacta (SNpc) that projects their axons to the dorsal striatum regulating cortical innervations of medium spiny neurons. Dysfunction in dopaminergic neurotransmission within the striatum leads to movement impairments, gaiting defects, and hypo-locomotion. Due to their high polarity and extreme axonal arborization, neurons depend on molecular motor proteins and microtubule-based transport for their normal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…hsa-miR-142-3p and hsa-miR-199a-3p identified in the present study have been experimentally shown to regulate KIF5B 55,56 . KIF5B is a motor protein in the dopaminergic synapse pathway and a member of the kinesin superfamily (KIF) 57,58 . KIF5B working with DISC1 is associated with the axonal transport of synaptic cargoes 59 and is involved in neuron dopamine metabolism 58 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…hsa-miR-142-3p and hsa-miR-199a-3p identified in the present study have been experimentally shown to regulate KIF5B 55,56 . KIF5B is a motor protein in the dopaminergic synapse pathway and a member of the kinesin superfamily (KIF) 57,58 . KIF5B working with DISC1 is associated with the axonal transport of synaptic cargoes 59 and is involved in neuron dopamine metabolism 58 .…”
Section: Discussionmentioning
confidence: 99%
“…KIF5B is a motor protein in the dopaminergic synapse pathway and a member of the kinesin superfamily (KIF) 57,58 . KIF5B working with DISC1 is associated with the axonal transport of synaptic cargoes 59 and is involved in neuron dopamine metabolism 58 . Some studies suggest that dopamine dysregulation is a mechanism underlying PLE 60,61 .…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting finding from the proteomics study was the increased expression of KIF5B in the hippocampus of L-lactate-treated rats. KIF5B is the main kinesin motor driving anterograde mitochondrial axonal transport in neuron ( Lackner, 2014 ; Cromberg et al, 2019 ). Previous studies showed that KIF5B is crucial for dendritic spine morphogenesis, synaptic plasticity, and memory formation ( Cai et al, 2007 ; Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although not furnished in this particular study, the impairment of KIF5-mediated neuronal transport would most likely also affect mitochondrial trafficking, as these are the motor proteins involved in the axonal anterograde transport of mitochondria, as indicated by other studies. Impairment in KIF5-mediated axonal transport has also been directly linked with striatal dopaminergic neuronal loss [ 118 , 119 ]. Embryonic primary neuron cultures lacking the CCP1 gene showed immense tubulin hyperglutamylation, and the time expenditure of anterograde and retrograde mitochondrial movement was reduced by 50% without any compromise in the run length or speed of transport [ 120 , 121 ].…”
Section: Ptms Of Tubulin – Limelight On Acetylationmentioning
confidence: 99%